Larvicidal Activity of Plant Extracts on Aedes aegypti (L.) (Diptera: Culicidae), under Laboratory Conditions - Coelho, André A.M.; Paula, José E. de; Espíndola, Laila S. (BioAssay, 2009)
Dengue is a virus bourne disease, chiefly transmitted by Aedes aegypti (L.) (Diptera: Culicidae) mosquitoes. Vector control remains as the best prophylactics. However, some populations have shown significant levels of resistance to several pesticides, indicating the need of new insecticides for the control of these insects. Insecticidal activity of 67 Cerrado plant extracts were assayed on third instar larvae of A. aegypti, under laboratory conditions. For the extract application, ten larvae, in triplicate, were placed into Petri dish containing 20 ml of solution (500 μg/ml). The insects were maintained at 28 ± 5°C, under 70 ± 5% relative humidity and 12h photophase. After 24 h the number of dead larvae was counted. The dichloromethane extract of the leaves of Kielmeyera coriacea Mart. (Clusiaceae) showed high toxicity against larvae of A. aegypti with LC50 values of 112.79 µg/ml. These data suggest that this extract should be chemically investigated and monitored through biological assays in order to determine their insecticidal components that could be used as a molecular model or as biorational compounds for use in insect control programmes.